STRATEGI ASEAN CAPITAL MARKET FORUM (ACMF) DALAM UPAYA MENDORONG TERWUJUDNYA INTEGRASI PADA SEKTOR PASAR MODAL DI KAWASAN ASEAN PADA TAHUN 2008 – 2015 - Wiguna, Ketut Gede; Fasisaka, Idin; Parameswari, A.A.A Intan (DIKSHI (DISKUSI ILMIAH KOMUNITAS HUBUNGAN INTERNASIONAL), 2017)
ABSTRACT This research aim to describe the strategy of ASEAN Capital Market Forum (ACMF) to encourage capital market integration process in ASEAN since 2008 until 2015. Capital market integration is the one of the agreement on ASEAN Economic Community blueprint. ACMF as an epistemic community or group of expert on the capital market established as a group to encourage the capital market integration process based on the 13th ASEAN Financial Ministers Meeting decision. As an epistemic community, the members of ACMF consists of all financial service authority institutions in ASEAN to use power as epistemic community for encourage capital market integration process. This research discovered that when ACMF implement their strategy, ACMF role as influence giver to the decision maker. This will be a qualitative-descriptive research and uses several concepts like the concept of capital market integration and influence mechanisms of epistemic community. Keywords: ACMF, Capital Market Integration, Epistemic Community, Influence Mechanisms of Epistemic Community